Edukasi Perilaku Keuangan Pengenalan Fintech bagi Masyarakat agar Terhindar dari Bahaya Pinjaman Online - Wiwit Irawati; Tri Utami; Wiwit Setyawati (Abdimisi, 2021)
Nowadays online-based loans are rife along with the development of Financial Technology (Fintech) with the convenience access offered compared to borrowing from banks. Sufficient understanding is needed so that people are wiser in using online loans. This Community Service is carried out to housewives in the West Pamulang area, totaling approximately 40 people with the implementation method in the form of counseling or lectures, and discussions. The results of PKM activities obtained data that most of the participants knew about online loans but did not understand the risks that might arise if they chose the wrong online loan service. After participating in this activity, participants have learned the tips that must be done to avoid the trap of illegal online loans.